Limited war : - Osgood, Robert Endicott (The University of Chicago Press, 1957)
Contents: The present volume deals with a problem that goes to the very heart of Amerian foreign policy. How can the United States protect and promote effectively its interests on the international scene without running the risk of an all-out atomic war? How is it possible to conduct foreign policy in the shadow of the atomic deterrent without making of that deterrent a reality? It is on these fundamental questions that this book reflects, and it is to them that it ateempts to give at least tentative answers